Propuesta para la elaboración de un inhibidor de corrosión a partir de la borra de café para su aprovechamiento a nivel industrial (2022)
The purpose of this work is to obtain oil from coffee grounds at a laboratory scale to evaluate its properties as a possible corrosion inhibitor. Corrosion cannot be avoided, but its control is possible; and in order to find better products for corrosion inhibition and that are friendly to the environment, it is advisable to look for new products that meet these characteristics, such as oils of vegetable origin, due to the properties they possess and being a resource renewable increasing its importance by not having any harmful agent that affects the environment. Coffee is the second most consumed beverage globally and a sub-product for its preparation is coffee grounds, it was sought to use the oil present in it as a corrosion inhibitor where mass loss tests were used to verify its effectiveness in addition to identifying its properties.